The Effect of Preoperative Rehabilitation Training on the Early Recovery of Joint Function after Artificial Total Knee Arthroplasty and Its Effect Evaluation. (25th January 2022) - Zheng, Yuliu; Huang, Zida; Dai, Liqun; Liu, Yu; Chen, Yanqin; Zhang, Wenming; Lin, Rongjin
Abstract : Objective . To study the effect of preoperative rehabilitation training on the rehabilitation of patients after total knee arthroplasty. Methods . A total of 120 patients diagnosed with knee osteoarthritis and undergoing total knee arthroplasty were selected and divided into experimental group and control group according to a random number table, with 60 cases in each group. The control group only carried out routine clinical nursing before the operation, and the experimental group used the formulated preoperative rehabilitation training method based on the control group for training. By comparing the visual analogue score (VAS), keen society score (KSS), postoperative time to get out of bed for the first time, patient satisfaction, and other related indicators between the two groups of patients, the recovery of keen joint function of patients after surgery was evaluated. Results . The visual analogue scale (VAS) of the experimental group was significantly lower than that of the experimental group at three days after operation. The keen society score (KSS) of the experimental group was significantly better than that of the control group at three days after surgery and one month after surgery. The time to get out of bed for the first time after operation in the experimental group (44.93 ± 13.63) was significantly less than that in the control group (78.33 ± 13.52). The patient satisfaction of the experimental group was significantly higher than that of the control group (88.30 ± 3.61). The above statistical results were all p < 0.05 of the two groups, and the differences were statistically significant. Conclusion . Preoperative rehabilitation training can significantly reduce the pain of patients after knee replacement, improve the functional state of knee joints, shorten the time to get out of bed for the first time after surgery, and win the best recovery opportunity, which can better improve patient satisfaction in hospitalization and improve medical care services level.